2023
DOI: 10.3389/fnhum.2023.1160981
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of narrativity lead to similar patterns of posterior EEG activity across individuals

Abstract: IntroductionThe focus of cognitive and psychological approaches to narrative has not so much been on the elucidation of important aspects of narrative, but rather on using narratives as tools for the investigation of higher order cognitive processes elicited by narratives (e.g., understanding, empathy, etc.). In this study, we work toward a scalar model of narrativity, which can provide testable criteria for selecting and classifying communication forms in their level of narrativity. We investigated whether be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…We then explored whether individuals’ brain activity was modulated by their engagement levels throughout the dramatic arc model. We previously found that different levels of narrativity led to differences in ISC and different levels of perceived engagement, thereby predicting narrativity level ( Dini et al, 2023 ). Cohen et al (2017) evaluated time perception and its relation to engagement during narrative videos, from which they posited that engagement could be considered subject’s levels of similarity among EEG channels (i.e., ISC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We then explored whether individuals’ brain activity was modulated by their engagement levels throughout the dramatic arc model. We previously found that different levels of narrativity led to differences in ISC and different levels of perceived engagement, thereby predicting narrativity level ( Dini et al, 2023 ). Cohen et al (2017) evaluated time perception and its relation to engagement during narrative videos, from which they posited that engagement could be considered subject’s levels of similarity among EEG channels (i.e., ISC).…”
Section: Discussionmentioning
confidence: 99%
“…ISC is a data-driven method that correlates individuals’ neural data to others’ neural data to test whether participants perceive the same stimulus in similar ways and at the same time while neglecting subjective differences ( Nastase et al, 2019 ). ISC is an approach that is well suited to both EEG and fMRI datasets as it captures the stimulus-driven patterns of neural activity ( Simony et al, 2016 ; Petroni et al, 2018 ; Finn et al, 2020 ; Imhof et al, 2020 ; Dini et al, 2023 ). Moreover, to identify the brain regions’ patterns that are modulated by stimuli, ISC is considered an alternative method that overcomes the problems of traditional methods (e.g., general linear model) as it reduces intrinsic noises ( Simony et al, 2016 ; Song et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation